THE INFLUENCE OF AGE FACTOR AND SPORTS SPECIALIZATION ON THE LEVEL OF AGILITY IN SPORTS GAMES - Pavol HORIČKA (Cluj University Press, 2021)
Objectives: The aim of the study was to determine the influence of age factors and the type of sports specialization on performances in planned and reactive agility. The object of the research was 129 players of football, volleyball, basketball and handball from sports clubs in Nitra and its surroundings in the categories of boys U15 ( = 14.95r) and boys U 17 ( = 16.88r). Methodology: The level of planned agility (PA) was diagnosed by the Illinois test and the level of reactive agility (RA) by the Fitro agility Check test. Results: The results showed the importance of both factors (Sport specialization and age) on performance in PA and RA, higher values (p) for the age factor (p < 0.05). Conclusions: The biological mean (age) has affected performance in RA more strongly than a type of sports game. Post hoc tests between groups (sport specialization) confirmed the statistical significance of differences between sports games to the detriment of basketball (p < 0.01).